SMS APPLICATION FOR DESIGNING PATIENT REGISTRATION ONE IN HOSPITALS - Rahayu Noveandini (JAKSTIK Journal, 2006)
Technology exists to provide easiness of a problem faced by the community. One technology that is widely used and very popular by the current mobile phone users are SMS (Short Message Service). With SMS, it has many applications are implemented based on current SMS, such as quis, polls, forums, even for business applications as well as ordering products. At this writing, they invented a concept of patient information services to facilitate patients who want to go to a hospital, which consists of three types of service concepts, namely: patient registration service registration information, service information and service schedule doctor's advice and inputs for the improvement of health services disuatu TSB hospitals by patients. With the concept of this service, patients can register without having to go directly to a hospital, quite simply sending an SMS to the service of this information, it will automatically direct response by the patient's information services in a hospital using an SMS service infrastructure. Registration procedure is the same as in ordinary, only can be done anytime and from anywhere.Â